Nugget coombs : - Rowse, Tim (Cambridge Univesity Press, 2002)
HC Coombs was one of the most influential Australians of the twentieth century. Born in 1906, he is best known as the governor of the central bank, but the breadth of his activities and his commitment to public life until his death is unsurpassed. Tim Rowse traces Coombs' life from his childhood in Western Australia to his many roles as policy maker, change agent, advocate and adviser. This book covers Coombs' life from birth to death, providing intriguing insights into the life of one of Australia's most influential people.